Rocking the Boat of Hope, or tipping it over? : Vulnerability, gender ethics, and hope during a 21st century global pandemic - Kotzé, Manitza; Noeth, Carike (Stellenbosch Theological Journal, 2024)
SARS-CoV-2 has had a major impact on global humanity and is still a reality that we live with. While there are rays of hope that things may return to a new normal with less restrictions and a better understanding of the coronavirus (albeit still limited) and how to prepare for any new mutations or strains of the virus, or infectious waves due to new mutations, the pandemic has also brought several underlying issues to the fore. One of these is gender equality, with women in many instances being hit the hardest by some of the challenges brought about by Covid-19, such as the closing of schools and resulting childcare. In this article we will examine the vulnerability of women and girls before and during a global pandemic, including a theological perspective on the notions of vulnerability, dependence and relationality in this regard. The question we seek to address is whether the little boat carrying the hope for change in terms of gender equality has been only rocked, or whether it has been completely tipped over? We conclude with a theological reflection on hope as one of the pillars on which to build human life.